IMPLIKASI KOMUNIKASI MITIGASI BENCANA BERBASIS PENGGUNAAN SIMBOL KEARIFAN LOKAL DALAM PROGRAM KENTONGAN RRI DENPASAR - Pramana, Ida Bagus Ngurah Tri; I Nyoman Yoga Segara; I Wayan Wastawa (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
Radio Republik Indonesia (RRI) initiated the Kentongan broadcast program in the final quarter of 2019, focusing on disaster mitigation education. As it enters its fifth year of implementation in 2024, there are challenges in disseminating information on disaster mitigation. Targeting the Balinese community as the audience, the local wisdom symbols can be incorporated into radio broadcast programs as part of an integrated cultural preservation and disaster mitigation education. The formulation of the research problem in this study is to determine the implications of local wisdom symbols in the RRI Denpasar Kentongan program. The theory employed for analysis is the Hypodermic Needle Theory. The research uses a descriptive-verification research method with the research location at RRI Denpasar. Primary data is collected through in-depth interviews and observations, with informant selection using purposive sampling. Data analysis consists of four stages: data collection, data condensation, data presentation, and conclusion drawing. Data is presented in narrative text supported by graphs or tables. From the data analysis, it was found that the implications of disaster mitigation communication can be observed through the feedback provided by listeners. RRI Denpasar needs to maximize the implementation of the Kentongan program by maintaining the continuity of the program and addressing relevant disaster topics along with local wisdom to support the persuasion process.